2009
DOI: 10.1523/jneurosci.3266-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Release in Dissociable Striatal Subregions Predicts the Different Effects of Oral Methylphenidate on Reversal Learning and Spatial Working Memory

Abstract: Previous data suggest that methylphenidate can have variable effects on different cognitive tasks both within and between individuals. This is thought to be underpinned by inverted U-shaped relationships between cognitive performance and dopaminergic activity in relatively separate fronto-striatal circuits and reflected by individual differences in trait impulsivity. Direct evidence for this is currently lacking. In this study, we demonstrate for the first time that therapeutic doses of oral methylphenidate ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
181
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(208 citation statements)
references
References 55 publications
27
181
0
Order By: Relevance
“…We thus build on previous studies (Clatworthy et al, 2009;Cools and D'Esposito, 2011) in attempting to identify predictors of the variability in response to dopaminergic drugs such as MPH, which may help improve our mechanistic understanding of this clinically relevant compound.…”
Section: Discussionmentioning
confidence: 99%
“…We thus build on previous studies (Clatworthy et al, 2009;Cools and D'Esposito, 2011) in attempting to identify predictors of the variability in response to dopaminergic drugs such as MPH, which may help improve our mechanistic understanding of this clinically relevant compound.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dopamine-releasing stimulants are well known to improve cognitive function in both participants with ADHD and healthy individuals (Klorman et al, 1984;Elliott et al, 1997). However, multiple studies have shown that whether dopaminergic agents (particularly D2 receptor agonists), improve or impair cognitive function strongly depends on baseline measures (Kimberg et al, 1998;Mehta et al, 2004;Roesch-Ely et al, 2005;Frank and O'Reilly, 2006;Cools et al, 2009Cools et al, , 2007Clatworthy et al, 2009). For example, D2 stimulation generally improves performance in individuals with low working memory span (Kimberg et al, 1998;Frank and O'Reilly, 2006), or high impulsivity (Cools et al, 2007), or low baseline DA synthesis (Cools et al, 2009), whereas it impairs performance in those in the opposite groups.…”
Section: Individual Differences In Response To Pharmacological Manipumentioning
confidence: 99%
“…Furthermore, DA drugs can affect the degree to which working memory updating strategies are themselves learned across trials (Frank and O'Reilly, 2006;Moustafa et al, 2008b). Finally, a recent study showed that the extent to which stimulants cognitive function is predicted by drug-induced changes in D2 receptor availability in distinct striatal sub-regions, depending on the task (Clatworthy et al, 2009).…”
Section: Individual Differences In Response To Pharmacological Manipumentioning
confidence: 99%
“…Observations that dopamine agonists either improve or impair brain processes have been accounted for by using the inverted-U principle, that is, agonists might stimulate the dopamine system to 'optimal' or overdosed levels in individuals with low and high baseline dopamine system functioning, respectively (Cools, 2008;Cools and Robbins, 2004). Initially seen in the context of prefrontal D 1 R receptor stimulation, the inverted-U effect has also been extended to the striatal D 2 R system (Clatworthy et al, 2009;Cools et al, 2009;Phillips et al, 2004). Studies investigating the moderation of dopamine drug effects on brain activity and performance by variables that might index baseline dopamine levels have made use of the genetic variation associated with Taq1A DRD2 gene polymorphisms, and have observed a baselinedependency of dopamine drug effects on reward-related processing (Cohen et al, 2007).…”
mentioning
confidence: 99%